An Analysis of Discourse Marker Use in Informal Conversations among Non-Native English-Speaking Students - Amal, Rizal Alamsa; Hasan, Rifal (Institut Agama Islam Negeri (IAIN) Manado, 2025)
This study investigates the use of discourse markers (DMs) in male and female students’ speech, focusing on their frequency, function, and gender-based variation. It explores how DMs support coherence and fluency in spoken discourse within an educational context. Through a sociolinguistic lens, the study identifies patterns of DM usage and potential linguistic differences between genders in spontaneous speech. A qualitative descriptive approach was employed to transcribe and analyse audio-recorded student conversations. Discourse analysis was used to classify the types and functions of DMs. Findings show that both male and female students used DMs to structure discourse, manage turn-taking, and signal speaker stance. However, female students tended to use a wider range of DMs, particularly those expressing agreement, politeness, and elaboration. In contrast, male students more frequently used DMs associated with hesitation and topic shifts. These results underscore the influence of sociolinguistic factors in DM selection and highlight how gender can shape spoken language patterns.Keywords: sociolinguistic, discourse markers, spoken discourse, student speech